Release of alcohol oxidase 1 (AOX1) from Pichia pastoris during heterologous expression of rice enzymes - Nikmah, Istiftakhun; Kongdin, Manatchanok; Hua, Yanling; Roytrakul, Sittiruk; Fatchiyah, Fatchiyah; Ketudat-Cairns, James R. (Asia-Pacific Journal of Science and Technology, 2022)
Pichia pastoris is a popular host for recombinant expression of proteins due to its ability to secrete proteins, grow at high cell density with methanol as a carbon source, and support methanol-induced protein expression with the alcohol oxidase 1 (AOX1) promoter. However, overproduction of native proteins in the medium during induction may decrease its advantage as a host for heterologous protein expression. Here, we sought to identify what native protein is overexpressed in the medium during heterologous expression of rice enzymes in P. pastoris. The genes encoding rice enzymes, including Os4BGlu11 β-glucosidase and two putative serine carboxypeptidase-like acyltransferases, OsSCPL2a and OsSCPL7, were inserted in the pPICZαBNH8 expression vector and used to transform P. pastoris. Upon induction of expression, a 75 kDa protein was observed in the medium of cells expressing OsSCPL7 and Os4BGlu11 but not in OsSCPL2a. The protein was purified by immobilized metal affinity chromatography from the media, excised from sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) gels, and identified by liquid chromatography and tandem mass spectrometry (LC/MS/MS) as P. pastoris alcohol oxidase 1 (AOX1) protein. The purified AOX1 was found to convert cyanidin-3-O-glucoside to compounds that no longer exhibit absorbance in the 520 nm range, but absorb relatively strongly at 360 nm, as detected in ultra-high-performance liquid chromatography. These results suggest that although it is normally found in the peroxisome, AOX1 protein may be released into medium during expression of certain proteins, but not other closely related proteins, and that AOX1 has the ability to oxidize complex phenolic alcohols, such as anthocyanins.